If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 7 = x + -9 Reorder the terms: 7 + -2x = x + -9 Reorder the terms: 7 + -2x = -9 + x Solving 7 + -2x = -9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -2x + -1x = -9 + x + -1x Combine like terms: -2x + -1x = -3x 7 + -3x = -9 + x + -1x Combine like terms: x + -1x = 0 7 + -3x = -9 + 0 7 + -3x = -9 Add '-7' to each side of the equation. 7 + -7 + -3x = -9 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -9 + -7 -3x = -9 + -7 Combine like terms: -9 + -7 = -16 -3x = -16 Divide each side by '-3'. x = 5.333333333 Simplifying x = 5.333333333
| 1.95l=100+97+97+l | | y+6xy-1=a | | 2.5x+12=12 | | (8b+3c)(8b-3c)= | | 15=37-11x | | 3x=x/2+15 | | (3x+8)=28 | | 3366.7+1591.5+726.6+405.3+95+95+95+95+95+95+l=1.95l | | 3x/2-x/6=12 | | 13=7+2x | | 4x-6=2(x+7) | | 1591.5+726.6+405.3+95+95+95+95+95+l=1.95l | | 3x-2-12x=1 | | 726.6+305.3+100+95+95+95+95+l=1.95l | | 405.3+95+95+95+l=1.95l | | 3x-(-6)+x=6 | | log(x-1)+log(x-3)=log(3x-7) | | 36=4(2p-3) | | (2/54x^2)^2 | | (1/2-1/3) | | 9x^2-20x=20x-21x^2 | | 1(2x)(x)=0 | | 1.95l=621.4+95+95+95+95+l | | -12x=x+13 | | 1.95l=305.3+95+95+95+l | | 1.95l=195+95+l | | 5x+50=8x+15 | | (x^2-x+1)(x^2-x+2)-12=0 | | 1.95l=1609.6+95+95+95+95+95+95+l | | 1.95l=1054.1+95+95+95+95+95+l | | 2*8+2*3=60 | | 1.95x=621.4+95+95+95+95+x |